Catalytic performance of Co–Fe mixed oxide for NH3-SCR reaction and the promotional role of cobalt. Issue 70 (13th July 2016) - Shao, Changzhi; Liu, Xiaofei; Meng, Dongmei; Xu, Qian; Guo, Yanglong; Guo, Yun; Zhan, Wangcheng; Wang, Li; Lu, Guanzhong
Abstract : Co-modified iron oxide (Co-FeO x ) catalysts were prepared by a citric acid method for the low temperature NH3 -SCR of NO in the presence of O2 . Abstract : Co-modified iron oxide (Co-FeO x ) catalysts were prepared by a citric acid method for the low temperature NH3 -SCR of NO in the presence of O2 . The results show that the amount of Co obviously influences the activity and stability of the Co-FeO x catalyst for the NH3 -SCR reaction, and when the molar ratio of Co/Fe is 0.2 (Co–Fe-0.2), NO is completely converted at 170 °C and the operation temperature window reaches 210 °C. After eight reaction cycles, the NO conversion and operation temperature window are hardly changed, and the presence of Co can markedly increase both its SO2 and H2 O resistance ability. It was found that doping Co into α-Fe2 O3 results in the formation of CoFe2 O4 crystals, and increases the relative content of Fe 3+, surface oxygen amount and oxygen activity. The Co–Fe-0.2 catalyst has the smallest particle size and the largest surface area, and possesses higher reducibility and catalytic activity for NO oxidation to NO2 than α-Fe2 O3, resulting in an improvement of the "fast-SCR reaction".